Project-Based Learning in Science Learning: A Philosophical Perspective of Realism in Madrasah Ibtidaiyah - Mutiya, Khoiru; Maemonah, Maemonah; Septiana, Nyangfah Nisa (Universitas Islam Lamongan, 2025)
The philosophy of realism in education emphasizes direct experience and observation of concrete phenomena as the foundation of knowledge. This principle aligns closely with Project-based Learning (PjBL), which engages students in authentic tasks to solve real-world problems. This study analyzes the application of PjBL in grade 5 Natural Science learning at a Madrasah Ibtidaiyah in Yogyakarta and identifies factors influencing its implementation. Using a descriptive qualitative approach, which includes observation, interviews, and documentation, the findings reveal that PjBL reflects the principles of realism, as students construct knowledge through active participation and direct interaction with real phenomena. Teachers implemented PjBL through six stages, culminating in a project to create a simple lung model. This activity enabled students to understand the respiratory system through empirical observation, rather than memorization, by examining their breathing patterns before and after engaging in physical activity. PjBL enhanced conceptual understanding, practical skills, critical thinking, and creativity. High student engagement, teacher creativity, and institutional support facilitated implementation, while time limitations, scarce resources, and limited teacher knowledge presented challenges.